CLINICAL CASES OF RECOVERY TECHNOLOGY GENTLE BITE HEIGHT IN PATHOLOGICAL ABRASION - R.V. Kozak (Ukrainian Medical Stomatological Academy, 2015)
The abstract. In pathological abrasion of teeth doctor before the problem arises not only recover lost hard tissue of teeth, and keep and received the maximum height for a long period of time. More patients pay attention to cosmetics designs, so recovery bite height is rather urgent problem today. Purpose: to conduct clinical trials of our proposed method of recovery bite height with pathological abrasion of teeth provided gentle preparation of hard tissues. Materials and Methods: consider it necessary to cite extracts from case histories of patients the second and third research groups, patients who's restored chewing rows respectively ceramic tabs and photopolymer materials. Example 1 Clinical diagnosis of decompensated generalized form horizontal pathological abrasion of teeth, stage 2 (classification MG Bushana). The patient was asked to manufacture ceramic tabs on chewing group of teeth and tooth restoration frontal area. Pre purified using a tooth brush we pickled enamel and dentin etching gel raincoat according to the instructions. Then the dried surface portions are making cement lining and lightly pressing fix their teeth. Then perform restoration of all other dental curing composite material EsthetX company "Dentsply" (Germany) by the conventional method. Finally check occlusal relationship and make recommendations to the patient who received further use designs. Recommended kept three days of eating, which is able to change the color of the reconstituted hard tissue of teeth. For controlling the inspection, visit a physician at 1 month, 6 months and 1 year after treatment. Example 2. Clinical diagnosis of decompensated generalized form horizontal pathological abrasion of teeth 2 degrees (classification MG Bushana). Patient proposed restoration of lost tissue chewing teeth and front groups photopolymer composite material EsthetX company "Dentsply" (Germany). Dental restoration was conducted by the conventional method. According electroodontodiagnosis pulp restored tooth surfaces reacts to stimuli that come close to those of the control group, and functional studies using electromyography indicate rapid addiction to the restored height of bite. Odontometryc past studies have shown that restoring dentition with generalized form of pathological abrasion of teeth chewing tabs ceramic group in conjunction with the restoration of the front much longer holds intraalveolyar height than the full restoration of dentition photopolymer material. So, in the article the clinical examples to compare two different methods of recovery bite height (conventional and our proposed) on the horizontal pathological abrasion, for further comparison of the results. We obtained full restoration of height of bite cosmetic designs provided most gentle preparation of dental hard tissues patients.